Top 10 Research Questions related to physical activity in preschool children - Pate, R.; O'Neill, J.; Brown, W.; McIver, K.; Howie, Erin; Dowda, M. (American Alliance for Health, Physical Education and Dance, 2013)
The purpose of this article was to highlight important research needs related to physical activity in 3- to 5-year old children. We identified research needs in 3 major categories: health effects, patterns of physical activity, and interventions and policies. The top research needs include identifying the health effects of physical activity, the effects of physical activity on the development of healthy weight, the effects of physical activity on learning and behaviour, and the health implications of sedentary behaviour. Research questions concerning patterns of physical activity include determining the prevalence of 3- to 5-year olds meeting the current physical activity guidelines; the social and environmental factors that influence physical activity in home, preschool, the community settings; and how physical activity tracks into later childnood, adolescence and adulthood. Research questions about interventions and policies include identifying the most effective strategies to promote physical activity in home, childcare and community settings and to reach diverse populations of young children, identifying effective intervention implementation and dissemination strategies, and determining the effectiveness of national, state, local and institutional policies for increasing physical activity. In conclusion, research is needed to establish a full understanding of the health implications of physical activity in 3- to 5- year old children, to better understand the nature of physical activity behaviour in this group, and to learn how to promote physical activity in young children.